Automated Drugs Dispenser Machine (ADM) - Ta'amra, Mu'min; Khalid, Obayda (Palestine Polytechnic University , mechanical engineering , mechatronics, 2017)
One of the most important pillars of community development is to improve the healthcare section. This includes facilitating the access to medications and drugs for all people and over the time. However, many people still have many di culties in obtaining their medications and drugs. Especially in rural places and at late night times or in Fridays. The Automated Drugs Dispenser Machine (ADM) is a new machine which allows patients to get their medications easily 24 hours a day, 7 days a week and in all places. The ADM has new characteristics that di er from other similar machines. This includes the working mechanisms, compatibility and the building costs. This machine consists of a combination of mechanical and electrical parts that work with each other harmonically to do the dispensing process e ciently and as required. The design of the ADM is required to achieve a high level of safety and accuracy in dispensing drugs. So, this machine will support the barcode reading feature in order to verify each medicine type before dispensing it. This process also requires a prescription and a special card for each patient to be able to use this machine. This machine will enhance the pharmacy operations and improve the healthcare section in the community. So that all people could get their medications easily at any time and wherever they live.
CD , 30290 , ميكاترونيكس 2/2017 , no of pages 164 , in the store
Keywords: Automated Drugs Dispenser Machine